Respuesta :
Step-by-step explanation:
first term (t1) = 6 (a)
Second term (t2) = - 18
Common ratio (r) = t2/ t1 = - 18 / 6 = -3
Now
14th term (t14)
=
[tex]a {r}^{14 - 1} [/tex]
[tex]6 \times ( - 3)^{13} [/tex]
= 6 X - 1594323
= 9565938
The 14th term of the geometric sequence 6, -18,54, ... is -9,565,938
Geometric series
Given:
6, -18, 54, ...
- First term, a = 6
Common ratio, r = a2 ÷ a1
= -18 / 6
= -3
- nth term of a geometric series = ar^n -1
14th term = 6 × -3^(14-1)
= 6 × -3^13
= 6 × -1,594,323
= -9,565,938
Therefore, 14th term of the geometric sequence 6, -18,54, ... is -9,565,938
Learn more about geometric series:
https://brainly.com/question/2899779